Dampak globalisasi terhadap pola hidup masyarakat di era digital - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2025)
The lifestyle of society has changed significantly with the advent of globalization and the digital era. The digital era has brought profound changes in the way humans interact. Because all of this is influenced by globalization that spreads rapidly through social media. Lifestyle in the present time has many broader choices. The research method used in this study is a qualitative research method, specifically the literature study method. The data collection technique is based on various journal literature. This research aims to observe various phenomena of lifestyle changes from a simple life to a modern lifestyle influenced by incoming cultures and the emergence of new cultures. Moreover, this journal highlights the detrimental effects on society if all of this is not responded to properly. Then it will cause the community to be negatively impacted, and if the community responds or processes it wisely, the community will gain positive benefits from globalization in the digital era.